EMBEDDED BASED WOMAN SAFETY INFORMATION SYSTEM - Manohar, Gunaselvi; Stanley, Pearley; Lakshmi, R.; Preethi, S. (International Journal of Psychosocial Rehabilitation, 2019)
Women are the assets of the nation. Women Safety is the major concern all over the World. Safety for women has become mandatory for all womanhood right from children to adults. Safety is necessary both inside and outside the home. Even though the world is heading towards modernization and equity of men and women, still there are many crimes against women. Nowadays, crimes against women especially physical abuse cases are getting high in range. We all know Delhi Gang rape and murder case was one of the most brutal case not only in India but also in the world. These cases are still happening all over the world and women are facing insecurity when it comes to harassment. This project “Embedded based women safety information system” proposes a quick responding mechanism that helps women during trouble. This project focuses on the security for women so that they will never feel helpless. This device is a wired control system equipped with an electronic weapon which is used to activate an electric shock to the attacker. The device consists of a band which carries the Arduino microcontroller and it is activated when the woman in trouble. When a stranger is going to attack a woman or physically abuse her, a touch signal will be sent to the microcontroller and simultaneously a voice keyword from the woman is sent to the microcontroller. Once the two inputs are received, the microcontroller gets ready to produce the outputs. An emergency message is given to the nearby police station along with an alarm buzzer ringing. Also, an electric shock signal is generated to the attacker thereby ensuring immediate safety to the innocent woman. Thus this device would be of great use to the women society and serves as a tool when she is in danger